2019
DOI: 10.1186/s13722-019-0135-7
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a pragmatic trial of the Consult for Addiction Treatment and Care in Hospitals (CATCH) model for engaging patients in opioid use disorder treatment

Abstract: Background Treatment for opioid use disorder (OUD) is highly effective, yet it remains dramatically underutilized. Individuals with OUD have disproportionately high rates of hospitalization and low rates of addiction treatment. Hospital-based addiction consult services offer a potential solution by using multidisciplinary teams to evaluate patients, initiate medication for addiction treatment (MAT) in the hospital, and connect patients to post-discharge care. We are studying the effectiveness of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 66 publications
0
32
0
Order By: Relevance
“…Combining two implementation frameworks to supplement one another is commonly used in the literature [ 59 62 ]. The CFIR is comprehensive regarding the assessment, and the RE-AIM framework is the intervention approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining two implementation frameworks to supplement one another is commonly used in the literature [ 59 62 ]. The CFIR is comprehensive regarding the assessment, and the RE-AIM framework is the intervention approach.…”
Section: Discussionmentioning
confidence: 99%
“…The RE-AIM evaluation framework may also be useful in implementing an intervention similar to ours on a larger scale. This framework was utilized by McNeely and colleagues to rigorously evaluate an OUD treatment consult model in a large multi-site trial, generating knowledge for how OUD treatment practices can be widely disseminated and adopted across healthcare systems [ 59 ]. Similarly, we may be able to apply our RE-AIM evaluation findings to larger scale interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The priority should be to ensure that all Medicare-certified SNFs are able to provide evidence-based medications, therapy, and counseling for patients with substance use disorders. A possible solution to reduce the burden for SNF staff who do not have expertise in substance use disorder treatment would be to develop addiction medicine consultant services, similar to ones developed for inpatient hospital settings [ 31 ]. These multidisciplinary teams could see patients with SUDs in the post-acute setting in SNFs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that evidence-based MOUD has superior outcomes in preventing mortality and decreasing opioid use (7). For this reason, we defined post-discharge OUD treatment engagement as: 1) at least two filled prescriptions for buprenorphine, extended-release naltrexone, or methadone from an Opioid Treatment Program in the 30 days following hospital discharge, or 2) a prescription for extended-release naltrexone or buprenorphine that covered 28 of the 30 days post-hospital discharge (24).…”
Section: Methodsmentioning
confidence: 99%